Implementation of Board Race Game in Improving Vocabulary of Grade 5 Student of Wakarleli Elementary School - Tutleta, Surlina Fanbora Tutleta Surly; Hukom, Salmon James; Kamanasa, Louisa Sarah (Prodi Pendidikan Bahasa Inggris, Program Studi Diluar Kampus Utama (PSDKU) Unpatti-MBD, 2024)
This study aims to improve the vocabulary acquisition of Grade 5 students at Wakarleli Primary School through the implementation of the Board Race Game. The research employed a Classroom Action Research (CAR) design, involving 22 students, and was conducted in two cycles, each consisting of four stages: planning, action, observation, and reflection. Data were collected through observations, vocabulary tests (pre-test and post-test), and interviews to evaluate the effectiveness of the game in enhancing students' vocabulary mastery. Each cycle included four meetings where the Board Race Game was integrated into the learning activities. The results indicated a significant improvement in students' vocabulary acquisition, along with increased student engagement and motivation in the learning process. This study contributes to the development of more effective, interactive, and engaging vocabulary teaching strategies, while also addressing knowledge gaps regarding the use of game-based learning in language instruction